Spontaneous intramural hematoma of the small bowel in anticoagulated patients—Insights into management: A case report - Ali Hajihashemi, MD; Hadi Khanifar, MD; Mahsa Geravandi, MD (Radiology Case Reports)
Intramural hematoma of the small bowel is a rare but potentially life-threatening complication of anticoagulation therapy, most commonly associated with warfarin use. This report presents two cases highlighting the clinical presentation and management of this condition. The first case involved a 72-year-old male with a history of heart valve replacement who presented with severe abdominal pain, nausea, and vomiting; imaging revealed a jejunal intramural hematoma and a significantly elevated INR. The second case involved a 51-year-old female with atrial fibrillation who experienced acute abdominal pain and partial bowel obstruction; CT imaging showed an intramural hematoma in the ileum with associated hemoperitoneum. Both patients were treated conservatively through cessation of warfarin, administration of vitamin K, and transfusion of fresh-frozen plasma, with one requiring surgical exploration but no bowel resection. Full recovery was achieved in both cases, and patients were safely transitioned to direct oral anticoagulants with no recurrence. These cases underscore the need for prompt diagnosis and multidisciplinary management in anticoagulated patients presenting with abdominal symptoms to prevent serious complications and improve outcomes.